Proton pump inhibitors and gut microbiota dysbiosis: insights into the pathogenesis of ulcerative colitis - Cao, Feng; Liu, Zhenxin; Liu, Shuo; Liu, Yanwei; Qi, Yong; Cheng, Yunsheng; Wang, Yong; Xu, Yanyan (Frontiers in Microbiology, 2025)
BackgroundUlcerative colitis (UC) is a chronic, relapsing inflammatory bowel disease characterized by continuous mucosal inflammation of the colon and rectum. The global prevalence of UC has been rising steadily, and accumulating evidence suggests a potential association between proton pump inhibitor (PPIs) use and UC development. Nevertheless, the precise role of PPIs in the pathogenesis and clinical course of UC remains unclear.MethodsThe C57BL/6J mice were administered saline, omeprazole (OME) and dextran sulfate sodium to establish control, PPIs-treated and UC models, respectively. The fecal samples were subjected to high-throughput sequencing of the V3-V4 hypervariable regions of the 16S rRNA gene. Taxonomic annotation was performed using Mothur software to evaluate microbial diversity and abundance. Principal coordinate analysis, linear discriminant analysis effect size, and functional enrichment analyses were also conducted.ResultsAlpha and beta diversity analyses showed that the richness and diversity of the gut microbiota in the PPI and UC groups were significantly lower than those in the control group (p < 0.05). At the family and genus levels, the UC group was dominated by Bacteroides, while the PPIs group exhibited enrichment of Eisenbergiella and Prevotella. Furthermore, functional enrichment analysis demonstrated that the gut microbiota in the PPI group was predominantly enriched in functions related to cell wall and membrane structure biogenesis, whereas the UC group was enriched in energy metabolism.ConclusionLong-term PPI exposure profoundly alters the gut microbiota, characterized by reduced microbial diversity and enrichment of pro-inflammatory taxa. These findings highlight the contribution of PPIs to gut microbiota dysbiosis and UC pathogenesis, emphasizing the need for further research on microbiota–immunity interactions and for the development of targeted strategies to mitigate PPI-related adverse effects.